Synergy of Research Paradigms and Critical Theory in an Action Research Study - Matsekoleng, Tsebo Kgoto; Mapotse, Tomé Awshar (Studies in Learning and Teaching, 2025)
The study explores the synergy of research paradigms comprising the living education paradigm, action learning paradigm, action science paradigm, and cooperative paradigm with critical theory in an action research study. This is supported by the explanation in Figure 4. Action research changes situations that people encounter in their everyday activities. Purposive sampling was used to select Grade 8 Technology Education (TE) teachers. Thirteen TE teachers from seven public schools participated in the study through the emancipation action research approach. Data were generated through observations and interviews. In collaboration, TE teachers were engaged in Progressive Environmental Action Research (PEAR) activities. The study found that TE teachers experience challenges in schools, including the integration of environmental matters into their subject. The implementation of PEAR activities addressed teachers’ challenges in their schools and shared insights on the synergy of research paradigms and critical theory. There is a synergy between research paradigms and critical theory, where identified problems are turned into workable solutions. Applying the research paradigms and the critical theory in TE has implications for teaching and learning in schools. The study’s findings are useful for TE teachers and other stakeholders when planning activities that promote collaborative learning, as advocated by research paradigms and critical theory.